Equity in transit-oriented development (TOD): a thematic and policy analysis of Chicago’s plans - Hughes, Jessica (My University, 2025)
This research analyzes the extent to which the priorities of Chicago’s regional transit-oriented development (TOD) plans address equity-related concerns. While TOD is promoted as a sustainable urban tool, offering benefits such as increased transit accessibility, modernization, and walkability, there are potential equity concerns. As cities adopt TOD strategies to improve public transit access and mobility, there have been critiques about who benefits and who does not. This qualitative research utilizes existing secondary data from five Chicago region plans, published between 2010 and 2022. Using thematic and policy analyses, similar themes and policy recommendations were identified to understand how Chicago frames and addresses priorities, rather than evaluating outcomes from policy implementations. All five plans agreed that key priorities are the preservation of affordability, increasing mobility, strengthening the transit system, accessibility, and expanding pedestrian-friendly communities. The plans published from 2010 to 2016 did not prioritize equity but had broader goals for regional transportation. In contrast, the plans published from 2018 to 2022 shifted the region’s focus towards equity. This research aims to contribute to ongoing conversations about the effects of transit investments and whether Chicago mitigates or reinforces patterns of spatial inequalities, or if they represent equitable and inclusive development.
Keywords: Transit-oriented development; Equity; Chicago